Investigating the antioxidant, antibacterial, and antifungal properties of typha domingensis leaves assisted synthesized zinc oxide nanoparticles - Md. Suzon Ahmed; Md. Ariful Islam Setu; Atasi Goswami; Mst. Sabiha Sultana; Palash Kumar Dhar; Md. Rezaul Haque; Sagar Kumar Dutta (PLoS ONE, 2026)
Green-synthesized nanoparticles (NPs) offer unique properties over traditional approaches, with applications in coatings, catalysts, packaging, environmental cleaning, and medicine. This research involves the synthesis of Zinc oxide nanoparticles (ZnO NPs) utilizing aqueous leaf extract of Typha domingensis (locally known as Hogla pata) as a reducing agent. The biosynthesized NPs were then characterized using ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM), and energy-dispersive X-ray (EDX) spectroscopy. The XRD result revealed that the synthesized NPs were enriched with (101) facets, which were similar to the standard JCPDS card no 00-036-1451. The size of the ZnO NPs was determined from XRD data utilizing the Debye-Scherrer equation and found to be around 26.74 nm. Moreover, the SEM analysis showed that the shape of the NPs was agglomerated spherical. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical showed dose-dependent antioxidant activity against synthesized ZnO NPs, with an average IC 50 of 32.25 µg/mL. The antibacterial efficacy of green-synthesized ZnO NPs was assessed against fungal and bacterial pathogens in antifungal experiments. Colletotrichum sp. showed the highest sensitivity to ZnO NPs, with a 20 ± 0.80 mm zone of inhibition (ZOI) and 22.22% inhibition, whereas Fusarium sp. had a 17 ± 0.68 mm ZOI and 18.89% inhibition at a dosage of 2 mg/mL. ZnO NPs also exhibited antibacterial activity against two gram-negative bacteria, Coliform sp. and Salmonella sp. , both demonstrating a 12 mm ZOI and 13.33% inhibition at 5.0 mg/mL. These results demonstrate that ZnO NPs biosynthesized with Typha domingensis leaf extract exhibit versatile antimicrobial and antioxidant properties, offering a safe and sustainable alternative to synthetic compounds.